Investigation of Mother-to-Child Transmission of Hepatitis B in Yinchuan, China: Cross-Sectional Survey Study - Jie Gu; Yiyuan Xu; Jiao Yuan; Yuxiang Chen; Jingxia Luo; Cui Guo; Guanbin Zhang (JMIR Publications, 2024)
BackgroundHepatitis B poses a significant global public health challenge, with mother-to-child transmission (MTCT) being the primary method of hepatitis B virus (HBV) transmission. The prevalence of HBV infection in China is the highest in Asia, and it carries the greatest burden globally. ObjectiveThis study aims to critically evaluate the existing local strategies for preventing MTCT and the proposed potential enhancements by analyzing the prevalence of hepatitis B among pregnant women and their neonates in Yinchuan. MethodsFrom January 2017 to December 2021, 37,557 prenatal screening records were collected. Among them, 947 pregnant women who tested positive for hepatitis B surface antigen (HBsAg) near delivery and their 960 neonates were included in an HBV-exposed group, while 29 pregnant women who tested negative and their 30 neonates were included in an HBV-nonexposed group. HBV markers in maternal peripheral blood and neonatal cord blood were analyzed using the least absolute shrinkage and selection operator (LASSO) regression, logistic regression, chi-square test, t-test, and U-test. Additionally, to further evaluate the diagnostic value of HBsAg positivity in cord blood, we conducted an additional follow-up study on 103 infants who tested positive for HBsAg in their cord blood. ResultsThe prevalence of HBV among pregnant women was 2.5% (947/37,557), with a declining trend every year (χ²4=19.7; P=.001). From 2018 to 2020, only 33.0% (35/106) of eligible pregnant women received antiviral medication treatment. Using LASSO regression to screen risk factors correlated with HBsAg positivity in cord blood (when log [λ] reached a minimum value of -5.02), 5 variables with nonzero coefficients were selected, including maternal hepatitis B e-antigen (HBeAg) status, maternal hepatitis B core antibody (HBcAb) status, maternal HBV DNA load, delivery method, and neonatal birth weight. Through univariate and multivariate logistic regression, delivery by cesarean section (adjusted odds ratio [aOR] 0.52, 95% CI 0.31-0.87), maternal HBeAg positivity (aOR 2.05, 95% CI 1.27-3.33), low maternal viral load (aOR 2.69, 95% CI 1.33-5.46), and high maternal viral load (aOR 2.69, 95% CI 1.32-5.51) were found to be strongly associated with cord blood HBsAg positivity. In the additional follow-up study, 61 infants successfully completed the follow-up, and only 2 were found to be infected with HBV. The mothers of both these infants had detectable HBV DNA levels and should have received standard antiviral therapy. The results of the hepatitis B surface antibody (HBsAb) positivity rate and titer test indicated a gradual decline in the immunity of vaccinated infants as the interval after vaccination increased. ConclusionsThe clinical relevance of HBV marker detection in cord blood is restricted within the current prevention measures for MTCT. There is an emphasis on the significance of public education regarding hepatitis B and the reinforcement of postnatal follow-up for the prevention of MTCT.